An Overview of the Population Dynamics Model Based on Climate Parameters - Syahrizal Koem; Rakhmat Jaya Lahay; Moch Rio Pambudi (Universitas Negeri Gorontalo, 2023)
Understanding how the environment, especially climate, affects the growth of pests (life cycle) is very important to create management techniques that reduce or eliminate damage to rice plants and minimize the resulting losses. This study aims to describe population dynamics modeling based on the influence of climate parameters using the DYMEX software. Climate and life cycle characteristics, which can be processed in the DYMEX life cycle module, are two important elements in modeling the rice stem borer. Egg, larval, and imago populations exhibit a variety of climate-related effects. The larval stage is most visible in the month of MJJA, where rainfall intensity is low or during the dry season. This indicates that the larval stage can survive through diapause in the dry season. The correct numbers must be used to initialize and parameterize models created using DYMEX. Overall, DYMEX can produce good simulation results in all life stages of the modeled insects. However, obtaining good, precise simulation results requires the user's accuracy in building the model, especially the values of the input parameters. In addition, to test the results of the DYMEX simulation, it is necessary to validate them with the actual conditions of the population in the field.